AACC Guidance Document on Laboratory Investigation of Acute Kidney Injury. (11th May 2021) - El-Khoury, Joe M; Hoenig, Melanie P; Jones, Graham R D; Lamb, Edmund J; Parikh, Chirag R; Tolan, Nicole V; Wilson, F Perry
Abstract: Background: Acute kidney injury (AKI) is a sudden episode of kidney damage or failure affecting up to 15% of hospitalized patients and is associated with serious short- and long-term complications, mortality, and health care costs. Current practices to diagnose and stage AKI are variable and do not factor in our improved understanding of the biological and analytical variability of creatinine. In addition, the emergence of biomarkers, for example, cystatin C, insulin-like growth factor binding protein 7, and tissue inhibitor of metalloproteinases 2, and electronic notification tools for earlier detection of AKI, highlights the need for updated recommendations to address these developments. Content: This AACC Academy guidance document is intended to provide laboratorians and clinicians up-to-date information regarding current best practices for the laboratory investigation of AKI. Topics covered include: clinical indications for further investigating potential AKI, analytical considerations for creatinine assays, the impact of biological variability on diagnostic thresholds, defining "baseline" creatinine, role of traditional markers (urine sodium, fractional excretion of sodium, fractional excretion of urea, and blood urea-to-creatinine ratio), urinary microscopic examination, new biomarkers, improving AKI-associated test utilization, and the utility of automated AKI alerts. Summary: The previous decade brought us a significant number of new studies characterizing the performance of existing and new biomarkers, as well as potential new tools for early detection and notification of AKI. This guidance document is intended to inform clinicians and laboratorians on the best practices for the laboratory investigation of AKI, based on expert recommendations where the preponderance of evidence is available.